SAT0682 Prevalence of sarcopenia in patients with chronic inflammatory rheumatic diseases. (15th June 2017) - Tournadre, A; Jaffeux, P; Frayssac, T; Fan, A; Couderc, M; Dubost, JJ; Malochet-Guinamand, S; Mathieu, S; Tatar, Z; Jourdy, JC; Soubrier, M
Abstract : Background: Evaluation of sarcopenia is of major relevance because of these clinical repercussions on morbidity and mortality. Although the definition should include both low muscle mass and function, a combination of the 2 criteria was not reported in inflammatory rheumatic diseases (IRDs). Objectives: To determine in a cohort of IRDs the prevalence of sarcopenia using established combined criteria (EWGSOP) (1). Methods: Sarcopenia defined as both low muscle mass (skeletal muscle index (SMI) <7.26 kg/m 2 for men; <5.45 kg/m 2 for women) and impaired muscular function (handgrip strength or gait speed) (1) was assessed in active rheumatoid arthritis (RA), spondyloarthritis (SpA) and psoriatic arthritis (PsoA) patients before initiating first biologic. Body composition (DXA) and related factors were compared using univariate, multivariate and correlation analysis. Results: 148 patients were included (Table). Sarcopenia with decrease in muscle mass and function was observed in 5 RA (7.8%), one SpA (1.7%) and one PsoA (9.1%). Sarcopenia in terms of reduced SMI only (1) was not more frequent occuring in 5 RA (7.8%), 3 SpA (5.1%) and one PsoA (9.1%). Grip strength was decreased in RA as well as muscle mass compared to SpA and PsoA but the difference was no longer significant when adjusted on age, sex, disease duration (Table). Only fat distribution differed with a trunk/peripheral fat ratio higher in PsoA. In RA, lean mass was negatively correlated with disease duration and sedentary time. In SpA and PsoA, fat mass was correlated with age, disease activity, HAQ. HAQ and CRP level negatively correlated with lean mass. No association between treatments and body composition was observed. Conclusions: Sarcopenia with combined criteria (muscle mass and function) occurred in 7.8% of RA corresponding to the values of the general population aged over 70 years-old (2). Reduced muscle mass only was not highly prevalent and lower than that reported in elderly suggesting important cofactors such as functional limitations or muscle quality in sarcopenia associated with rheumatic diseases. References: Cruz-Jentoft AJ et al. Age Ageing 2010;39:412–23. Spira D, et al. Z Gerontol Geriatr 2016;49:94–9. Disclosure of Interest: None declared